The library and information science profession in 2009 - Tejada-Artigas, Carlos (Anuario ThinkEPI, 2010)
A picture of developments in the Library and information science profession in 2009 is presented. Topics included are professional skills, values, social image, scientific and professional activities: congresses, conferences, journals, distribution lists, associations and the specific labor market.
Keywords: Profession; Skills; Values; Social image; Scientific and professional activities; Associations; Labor market.